2003
DOI: 10.1136/ard.62.7.690
|View full text |Cite
|
Sign up to set email alerts
|

Overlap connective tissue disease, pulmonary fibrosis, and extensive subcutaneous calcification

Abstract: Swollen joint count 9.9 (6.8) 5.8 (7.5)* 2.3 (4.6)* PASI (psoriasis activity skin index) 12.1 (10.3) 1.7 (5.6)* 1.1 (2.7)* ESR (mm/1st h) 21.6 (15.5) 15.9 (9.4) 20.2 (20.4) CRP (mg/l) 0.9 (0.9) 0.7 (1.3) 0.2 (0.4)* *p<0.01 as compared with baseline (determined by t test for paired data).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Overlap connective tissue disease (CTD) occurs when the classification criteria for two or more ACTDs are met in the same patient. Overlap CTD is uncommonly associated with calcinosis cutis (20). In two patients reported by Chan et al (20) and six patients reported by Balin et al (5) with overlap CTD-associated calcinosis cutis, the lesions were localized to the extremities, hands, or feet and had a variable incubation from diagnosis of the primary disease.…”
Section: Overlap Undifferentiated and Mixed Connective Tissue Diseasementioning
confidence: 93%
See 2 more Smart Citations
“…Overlap connective tissue disease (CTD) occurs when the classification criteria for two or more ACTDs are met in the same patient. Overlap CTD is uncommonly associated with calcinosis cutis (20). In two patients reported by Chan et al (20) and six patients reported by Balin et al (5) with overlap CTD-associated calcinosis cutis, the lesions were localized to the extremities, hands, or feet and had a variable incubation from diagnosis of the primary disease.…”
Section: Overlap Undifferentiated and Mixed Connective Tissue Diseasementioning
confidence: 93%
“…Overlap CTD is uncommonly associated with calcinosis cutis (20). In two patients reported by Chan et al (20) and six patients reported by Balin et al (5) with overlap CTD-associated calcinosis cutis, the lesions were localized to the extremities, hands, or feet and had a variable incubation from diagnosis of the primary disease. Undifferentiated CTDs are a heterogeneous group with varying clinical and serologic features that have not yet reached classification criteria for a single ACTD.…”
Section: Overlap Undifferentiated and Mixed Connective Tissue Diseasementioning
confidence: 93%
See 1 more Smart Citation
“…This report predates the widespread recognition of IBM and could possibly be similar to our case. Subcutaneous calcification is described in dermatomyositis, but not in sIBM 9. There have been reports of an IBM/dermatomyositis overlap syndrome based mainly on muscle biopsy appearances suggesting the former, with a skin rash suggesting the latter, but none had subcutaneous calcification 10.…”
Section: Discussionmentioning
confidence: 98%
“…Considering overlap syndromes, calcinosis is uncommon and located on the extremities, hands, and feet [ 50 , 101 ]. UCTD is also rarely complicated by calcinosis formation after a mean time interval of 2.7 years from the primary diagnosis, mainly on the extremities, hands, and feet [ 102 , 103 ].…”
Section: Discussionmentioning
confidence: 99%